The Influence of the Project-Based Guided Inquiry Learning Model to Improve the Ability to Think Creatively About Environmental Pollution - Mutiara Hasna (Jurnal Pendidikan dan Psikologi: Pintar Harati, 2025)
The ability to think creatively is a 21st century skill that is really needed by students today. One of the learning models that can facilitate students in practicing creative thinking skills is the project-based guided inquiry model. The aim of this research is to determine the effect of a project-based guided inquiry model on students' creative thinking abilities about environmental pollution. This research was carried out at a public high school in Jakarta in January-June 2024. This type of research is quantitative with a quasi-experimental research method. The research sample was selected using simple random sampling. Based on hypothesis testing using an independent t-test, it was found that there was an influence of the project-based guided inquiry learning model on students' creative thinking abilities about environmental pollution. The influence of the project-based guided inquiry model on students' creative thinking abilities can be analyzed based on each learning syntax in the project-based guided inquiry model. The results of this research imply that the project-based guided inquiry learning model can be used as an alternative model by teachers to improve students' creative thinking abilities on environmental pollution